Relation of yields of soybean and maize to sulphur, zinc and copper status of soils under intensifying cropping systems in the tropical savannas of northeast Nigeria - Kwari, J.D.; Kamara, A.Y.; Ekeleme, F.; Omoigui, L.O. (2009)
Deficiencies of sulphur (S), copper (Cu) and zinc (Zn) are becoming prevalent under intensifying agricultural systems in north-eastern Nigeria. They are manifest in the partial or lack of response by crops to NPK fertilizers leading to a reduction in crop quality and yields. Data were collected on the initial available S, Cu and Zn contents of some samples from 0-15 cm depth from farmers’ compound fields (64) and bush fields (73) in 30 communities across three agro-ecological zones in north-east Nigeria. These were related to the grain yields of soybean and maize varieties from demonstration trials to assess if they are yield determinants of these crops. Available S content (range 5.10-18.49 mg kg-1) was moderate to medium status in over 80% of the fields within the region. This content significantly influenced yields of soybean (P = 0.0245) and maize (P = 0.0415) in bush fields in the Southern Guinea savanna (SGS) and maize (P = 0.0074) in compound fields in Sudan savanna (SS), thus indicating S was a determinant of the performance of these crops. Nearly all fields were deficient in Zn with a range of 0.002-1.47 mg kg-1. This had a significant effect on maize yields in compound fields (P = 0.0376) in SGS and in bush fields (P = 0.0090) in SS. Also available Cu content was deficient (range 0.001-0.274 mg kg-1) in over 83% of the soils and had a significant effect on soybean yields in compound fields (P = 0.0455) in SGS. The soils in north-east Nigeria were moderate in S but deficient in Cu and Zn and may require the application of NPK fertilizer containing these micronutrients for the cultivation of maize and soybean.